EVALUATION OF EARLY NON-INVASIVE RESPIRATORY SUPPORT EFFICIENCY IN MATURE NEWBORNS - V. Chijenas; Yu. S. Aleksandrovich; K. V. Pshenisnov; D. V. Prometnoy; Z. Paulauskene; Yu. V. Stasova (Вестник анестезиологии и реаниматологии, 2018)
Non-invasive respiratory support by continuous positive airway pressure (CPAP) is the most common management technique of the respiratory distress syndrome in newborns. Goal: to evaluate efficiency of non-invasive respiratory support by CPAP in mature newborns depending on the start of therapy. Materials and methods. 39 newborns were enrolled into the study. Depending on the start of respiratory support infants were divided into 2 groups: Group 1 (n = 14) – therapy was started during the first 10 minutes after birth, Group 2 (n = 25) – therapy was started after transfer to Newborns Intensive Care Department. Results. Group 1 had lower rates of SpO2 intermediately after birth and higher rates of oxygen and carbon dioxide tension in blood. In Group 2 the correlation (r = 0.559; p < 0.05) has been found between the number of disorders of the newborn and duration of stay in Newborns Intensive Care Department . No significant differences in the outcome were found between the groups. Conclusion: The start of the non-invasive respiratory support during first 30 minutes after the birth results in the positive clinical effect and favorable impact on the outcome of the disease.